PELATIHAN PEMBUATAN PETA DASAR DESA POKA MENGGUNAKAN SOFTWARE ARCGIS - Ratuluhain, Eva S.; Noya, Yunita A.; Kalay, Degen E.; Rijoly, Fredrik; Rumlus, Andrego J. (Pattimura University, 2025)
Base maps are one of the important elements in presenting detailed geospatial information about the physical conditions of an area, including complementary features such as roads, rivers, contours, administrative boundaries and land use, which are very much needed in the fields of spatial planning, spatial development, infrastructure development, disaster mitigation, to natural resource management. The purpose of this training is for participants to understand the basic concepts of mapping, master geospatial data collection and processing techniques, and be able to produce accurate and informative base maps. This training was held on Saturday, May 3, 2023 at the Nutrihub Kate-Kate Building, Ambon City, involving 12 participants consisting of young men and women from Poka Village. The training took place using a combination of methods, namely Theory, Discussion, and Direct Practice of making base maps using the ArcGIS application. The results of the training showed that the participants could understand the basics of map making and were able to make base maps using the ArcGIS application.